Usability Testing of the Web-Based Learning Resource Center Kumatalibi.com Using the System Usability Scale (SUS) Among Preservice Biology Teachers - Dede Trie Kurniawan; Sri Maryanti (International Journal of Learning Media on Natural Science (IJLENS), 2025)
Educational technology platforms and tools generally exhibit good to high usability, as measured by the System Usability Scale (SUS). Several studies indicate that usability scores are not significantly influenced by user demographics such as age, gender, or device type. However, factors like the subject matter, personality traits, and educational stage can sometimes affect perceived usability. This overview will delve into these aspects, highlighting key findings from relevant studies. This study aims to evaluate the usability of the web-based learning resource center Kumatalibi.com using the System Usability Scale (SUS) method, which consists of 10 standardized questions to assess a system's usability quality. A total of 101 preservice biology teacher students participated in the study. The results showed that the average SUS score was 73. Based on this score, the website received a grade of C, placed in the 70th percentile, categorized as "Good" in adjective rating, "Marginal" in acceptability, and classified as "Passive" based on its Net Promoter Score (NPS). These findings indicate that the learning website is generally acceptable to users; however, improvements are needed to enhance user satisfaction. Enhancing usability may lead to better learning outcomes for preservice biology teacher students.